Meningkatkan Pembelajaran Lompat Jauh Gaya Jongkok Melalui Media Bankas Pada Siswa Kelas V (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study to determine the improvement of learning outcomes with the game long jump longjump squat style through media used tires on students. This research method uses Classroom Action Research(CAR). Subjects were fifth grade students of SD Negeri 01 Kebojongan which amounts to 18 students.Theresults showed that the long jump squat force through media used tires can increase learning. In the initialconditions show learning results 44.44% (8 students who completed), at cycle 1 shows the results of study61.11% (11 students who completed) which means it has no increase from the initial condition but has notreached the expected target percentage, while in cycle 2 study results showed an increase of 83.33% (15 studentswho completed) which means it has reached the expected target percentage. Conclusions from this research isthe long jump squat style game through media used tires can improve learning outcomes long jump at the fifthgrade students of SD Negeri 01 Kebojongan District of Comal Pemalang Academic Year 2013/2014